A levator ani midurethral support via single vaginal incision technique to treat stress urinary incontinence: A case report - Lai-Yet Lam; Janice A. Santos-Cortes; Timothy K. O'Rourke, Jr (Elsevier, 2023)
Stress urinary incontinence affects more than one-fourth of adult women. The recommended surgical treatment involves the use of a synthetic mesh sling. Upon unsuccessful treatment using a mesh sling or when patients decline mesh, surgical treatments, including an autologous fascia sling, colposuspension, or bulking injections, are used. After unsuccessful treatment using three mesh slings, an autologous fascia sling, and a midurethral bulking agent, a patient was successfully treated with our modified Kelly plication technique.A 51-year-old woman with recurrent stress urinary incontinence had had three previous mesh midurethral sling exposures with complete mesh removals followed by one autologous fascia sling with severe infection. We initially treated her with a set of urethral bulking injections, which was also unsuccessful. She was successfully treated with our modified Kelly plication technique, which plicates levator ani muscles to support the midurethral instead of plicating the vesicovaginal fascia at the bladder neck. The patient remained continent four years after the performance of this technique and had reported no pelvic pain or dyspareunia. The technique is detailed in this paper. This single vaginal incision native tissue technique may be considered when mesh slings or alternative native tissue procedures are not feasible for patients, as in this case.